Anthropometric Characteristics and other Dietary Aspects of a Group of Spanish Women Looking for Weight Loss and Enrolled in a Weight Management Program - Magdalena Rafecas,; Laura-Isabel Arranz,; Mireia García,; Miguel-Ángel Canela ,; DIECA group, (Journal of Pharmacy and Nutrition Sciences, 2014)
Overweight is a health problem characterised as a higher than normal body weight due to an abnormal increase in body fat. Body weight adequacy is categorised using body mass index (BMI), however other parameters as fat mass (FM), waist circumference or waist to hip ratio, are relevant. Ideally, body composition should be calculated initially to evaluate changes during a dietary intervention for weight loss. Hunger experience is another parameter to take into account in order to succeed. The aim was to investigate and describe the characteristics of women seeking weight loss solutions. We organised an open program for people with body excess who wanted to lose weight. 252 women participated and answered to a dietary interview. Anthropometric measures of weight, height, body mass index, body fat, waist and hip circumference were taken. The mean age was of 36.84±7.29 years, and most of them, about 90%, have followed dietary programs for weight loss throughout their lives. They all wanted to lose weight in a range of 3 to 20 kilograms with a mean value of 11.49±6.01 kilograms. 123 women had a hunger profile of satiating behaviour and 129 a snacking one. The mean BMI was within overweight values, and mean fat mass was within obesity values. Waist and hip circumference were higher than normal in most of the participants and excess body weight perception and attitude were different. There is a need to tackle overweight and obesity individually, taking into account personal consciousness and expectancy, anthropometric measures and hunger experience.